2020
DOI: 10.1016/j.kint.2020.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of the effects of canagliflozin on kidney protection in patients with type 2 diabetes

Abstract: Canagliflozin reduced kidney disease progression in participants with type 2 diabetes in the CANagliflozin cardioVascular Assessment Study (CANVAS) Program. This analysis explored potential mediators of the effects of canagliflozin on kidney outcomes. The percent mediating effect of 18 biomarkers indicative of disease was determined by comparing the hazard ratios for the effect of randomized treatment from an unadjusted model and from a model adjusting for the average post-randomization level of each biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 41 publications
8
91
3
2
Order By: Relevance
“…Changes from baseline in laboratory parameters including lipids, hematocrit and hemoglobin, and analytes (magnesium, phosphate, uric acid) observed in this sub-study were consistent with the findings in other VERTIS program studies [38]. The increases in hemoglobin and hematocrit and decreases in uric acid may be important mediators of the beneficial effects of SGLT2 inhibitors on heart failure, CV death, and kidney events [39][40][41].…”
Section: Discussionsupporting
confidence: 87%
“…Changes from baseline in laboratory parameters including lipids, hematocrit and hemoglobin, and analytes (magnesium, phosphate, uric acid) observed in this sub-study were consistent with the findings in other VERTIS program studies [38]. The increases in hemoglobin and hematocrit and decreases in uric acid may be important mediators of the beneficial effects of SGLT2 inhibitors on heart failure, CV death, and kidney events [39][40][41].…”
Section: Discussionsupporting
confidence: 87%
“…31 Furthermore, SGLT2 inhibitors restore impaired tubuloglomerular feedback and reduce hyperfiltration in diabetes, which could preserve long-term kidney function and reduce hypoxia. 32,33 Prior long-term and large clinical trials of SGLT2 inhibitors have reported similar increase in haemoglobin and haematocrit over follow-up in patients with type 2 diabetes and relatively normal kidney function 13,34,35,36 These studies also demonstrated that changes in haemoglobin and haematocrit from baseline explained nearly half of the effects of SGLT2 inhibitors versus placebo on the risk of cardiovascular death, heart failure, and kidney failure. [34][35][36] These data suggest a strong association between erythropoiesis parameters with cardiovascular and kidney outcomes which is supported by the findings from the current analysis demonstrating that development of anaemia was statistically significantly associated with subsequent risk of kidney and cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…It has been estimated that the associated increase in systemic hematocrit (~5%) may be responsible for as much as 50% of the increase in patient survival observed in clinical trials (Inzucchi et al, 2018). Thus, mild renal hypoxia may protect the kidney, while initiating a systemic response (EPO derived erythrogenesis), which may improve systemic oxygen delivery and organism survival (Inzucchi et al, 2018;Li et al, 2020). With respect to other studies which report measurement of renal P k O 2 utilizing different experimental models; these studies have a number of limitations.…”
Section: Discussionmentioning
confidence: 99%